"Dajati pobudo, priložnost in navad pravilnim telesnim vajam" (ob 150-letnici ustanovitve prvega slovenskega telovadnega društva Južni Sokol) - Pavlin, Tomaž (Šport (Ljubljana), 2013)
On 1 October 1863 the founding general meeting of the first Slovenian gymnastics society was held in Ljubljana and the society was named "Južni Sokol" (Southern Sokol). Its activities started already in 1862, soon after the Czech gymnastics society "Sokol" was organised in Prague. Južni Sokol was the pioneer of the Sokol movement in Slovenian territory, a mass civil-society movement and the precursor of the modern set of physical exerciseelements which was presented in the first Slovenian expert manual entitled "Nauk o telovadbi" (Lessons in Gymnastics) in 1867. The Slovenian Sokols, unlike many European nations which named a similar activity "gymnastics", with the Germans even using "turnen", named this activity with a Slovenian term "telovadba" (physical exercise). The gymnasts from Ljubljana spoke about the Slovenian gymnastic terminology already at the founding general meeting, but needed several years to implement it. The article deals with the organisation of the activity and the origin of the Slovenian term "telovadba", and explores whether the motive for the organisation was the Czech model or influence, which is a stereotype often stated in the Slovenian literature.
Keywords: Costa, Etbin Henrik, 1832-1875; gimnastika; gymnastics; Južni Sokol; physical exercises; Sokol activity; sokolstvo; sport; šport; telesne vaje; telovadba; zgodovina športa